CHILD GROWTH DEVELOPMENT AND EDUCATION IN WEST NUSA TENGGARA PROVINCE - sudirman, sudirman; Wibowo, Lindawati; Apriatni, Mandri; Sayuti, Rosiady; Muadz, Husni; Prado, Elisabeth; Shankar, Anuraj (Universitas Qamarul Huda Badaruddin, 2019)
The Government of West Nusa Tenggara (GoWNT) Province, Indonesia has proposed a “Golden Generation Program” (GGP) to support optimal child development. The GGP is supported by Provincial Decree No 7 (Provincial Development Planning Agency, 2011) to “Improve and Protect the Health and Welfare of Women, Infants and Children”. We propose a GGP that builds upon the existing collaborative efforts of the government, university and non-governmental organizations (NGO), to create an integrated intervention to increase the thrivability of young children by: Strengthening the existing Early Child Development Centers (ECDC) in each village with family centered approaches to increase caregiver capacities for health and early childhood development; Training and deploying developmental Community Development Worker (CDW) to coach and certify baby-friendly couples (BFC) for early childhood development; Deploying a mobile real-time data platform linking BFC, CDW, ECDC, Center for Early Child Development (CECD), Village health Post (VHP), and Primary Health Centers (PHC) to track infant growth and development and intervene if needed; Establishing a solid network that supports the CDW in carrying out their tasks on GGP. The network for sustainability plan of GGP includes a CDW Cooperative and link to any relevant institutes for ongoing support of ECD efforts. As a social business enterprise, the CDW Cooperative will gain revenue from insurance, goods and information provided to clients. With high variety of ethnicities and languages, efforts undertaken to design programs in Indonesia must be strongly based on local empirical evidences. A thorough formative research is then unexceptional for program success within the country. In the real situation, this kind of research is frequently oversimplified or even skipped as an essential element of the program development. Here, we presented the risks of program policy misconception in the absence of a formative research. Data were collected through in-depth I nterviews with various key informants; policy document reviews; direct field observations; and survey among 1,051 caregivers of children aged 0-4 yo. Within West Nusa Tenggara Province, East and Central Lombok Districts were selected as study sites. A thorough formative research is a must to create an evidence-based policy.